Looking for reliable answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.

If x = y – 3 and y = z + 7, then x (in terms of z) = ?



Sagot :

Answer:

Let's convert all into one variable and then do lcm of them. So, this is the simplest method

Step 1:

X = 3y/4

Z = 7y/6

x:y:z = 3y/4 : y : 7y/6

x:y:z = 3/4 : 1 : 7/6

Do lcm of 4 and 6 it's 12 .so, multiply with 12.

x:y:z = 9:12:14

Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.